Topical Problems of Accounting of Fixed Assets - LARISA K. Nikandrova; GALINA А. Skachko (Учёт. Анализ. Аудит, 2019)
The fixed assets are among the most frequent types of assets of any enterprise, regardless of its industry sector, form of ownership, management and organizational-legal forms. The emergence of Provisions in the accounting of some objects raises a number of questions regarding their application, since regarding accounting as such, is not mentioned there at all, so this is becoming the reason of misunderstanding of their implementation in the domestic practice. Similar problems the accountants faced after the introduction of Chapter 25 of the Tax code of the Russian Federation, “Tax on profit of the organizations”. The Chapter established the rules of accounting for the purposes of calculating the tax base for tax on profit (tax accounting). The discrepancies which occurred as a result, as shown in the article, have no economic justification. Starting from 2011, many businesses ceased to create reserves for capital repair of their fixed assets, due to the fact that this year their establishment was abolished for accounting purposes, in accordance with the rules adopted by the PBU8/2010 “Estimated liabilities, contingent liabilities and contingent assets”, but for tax accounting purposes the formation of such reserves is still maintained. The situation was explained neither by accounting experts nor by tax experts.